2009
DOI: 10.3899/jrheum.081302
|View full text |Cite
|
Sign up to set email alerts
|

Phagocyte-specific S100A8/A9 Protein Levels During Disease Exacerbations and Infections in Systemic Lupus Erythematosus

Abstract: Serum levels of S100A8/A9 are significantly raised in SLE versus pSS patients and healthy controls and can be correlated to a disease activity index. S100A8/A9 is a more relevant marker of infection in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 26 publications
6
80
1
2
Order By: Relevance
“…INOS regulates the production of cytotoxic NO, which are essential for defense against intracellular pathogens but also can promote host tissue damage if produced at exaggerated levels (38,39). S100A8, a protein whose serum levels correlate with SLE disease activity (40), has been demonstrated to trigger inflammation through direct binding of the TLR4/MD2 complex, a process shown to amplify other innate immune cell activation signals (e.g., LPS stimulation) (41). Based on these and other observations we propose a model for inflammatory disease development in which a low level of TLR stimulation (e.g., through TLR agonists released upon minor tissue injuries or through commensal bacteria) leads to increased production of described C/EBPβ-target genes.…”
Section: Discussionmentioning
confidence: 99%
“…INOS regulates the production of cytotoxic NO, which are essential for defense against intracellular pathogens but also can promote host tissue damage if produced at exaggerated levels (38,39). S100A8, a protein whose serum levels correlate with SLE disease activity (40), has been demonstrated to trigger inflammation through direct binding of the TLR4/MD2 complex, a process shown to amplify other innate immune cell activation signals (e.g., LPS stimulation) (41). Based on these and other observations we propose a model for inflammatory disease development in which a low level of TLR stimulation (e.g., through TLR agonists released upon minor tissue injuries or through commensal bacteria) leads to increased production of described C/EBPβ-target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Burri et al (6) , Abdel-Razik et al (18) , and Ali et al (23) , found that ascitic calprotectin levels were correlated well and reliably with ascitic PMNL counts, and the samples with PMNL > 250/μL also had higher ascitic calprotectin levels than the samples with PMNL ≤ 250/μL in their studies. The correlation between high serum & ascitic calprotectin with high ascitic TLC and PMNL levels can be explained by the study of Soyfoo et al (9) , who denoted that calprotectin presence in body fluids is proportional to the influx of neutrophils. In our study, there was a significant positive correlation between serum calprotectin and CRP, and this result is in agreement with Rizk et al (26) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a low ascitic PMNL count (<250/mm 3 ) with positive culture can also occur in another SBP variant called monomicrobial non-neutrocytic bacterascites (7) . Calprotectin is an abundant, calcium-and zincbinding protein found mainly in neutrophils (8) , and its presence in body fluids is proportional to the influx of neutrophils (9) . It is an acute phase inflammatory reaction protein which exerts regulatory, antimicrobial and anti-proliferative functions.…”
Section: Spontaneous Bacterial Peritonitis (Sbp) Is Definedmentioning
confidence: 99%
“…Phagocyte-specific S100A8/A9 protein levels have also been under investigation [12,49]. High levels of S100A8/A9 were found in some inflammatory diseases as rheumatoid arthritis and juvenile rheumatoid arthritis and they correlate with active stages of the diseases [49,50] Soyfoo and co-workers [49] investigated the level of this marker in SLE patients.…”
Section: Phagocyte-specific S100a8/a9 Proteinmentioning
confidence: 99%
“…High levels of S100A8/A9 were found in some inflammatory diseases as rheumatoid arthritis and juvenile rheumatoid arthritis and they correlate with active stages of the diseases [49,50] Soyfoo and co-workers [49] investigated the level of this marker in SLE patients. They reported that serum levels of S100A8/A9 were are significantly raised in SLE versus primary Sjogren's Syndrome patients and healthy controls and could be correlated to a disease activity index (SLEDAI).…”
Section: Phagocyte-specific S100a8/a9 Proteinmentioning
confidence: 99%